(untitled) (Altre Modernità, 2015)
For the former colony, decolonization is a dialogue with the colonial past, and not a simple dismantling of colonial habits and modes of life. Nowhere are the complexities and ambiguities of this dialogue more evident than in the vicissitudes of cricket in those countries that were once part of the British Empire. In the Indian case, the cultural aspects of decolonization deeply affect every domain of public life, from language and the arts to ideas about political representation and economic justice. ln every major public debate in contemporary India, one underlying strand is always the question of what to do with the shreds and patches of the Colonial heritage. Some of these patches are institutional; others are ideological and aesthetic.